2008
DOI: 10.1210/me.2008-0044
|View full text |Cite
|
Sign up to set email alerts
|

Research Resource: Rapid Recruitment of Temporally Distinct Vascular Gene Sets by Estrogen

Abstract: Cardiovascular disease is the leading cause of mortality for both men and women in developed countries. The sex steroid hormone estrogen is required for normal vascular physiology. Estrogen functions by binding to intracellular estrogen receptors (ER), ERalpha and ERbeta, ligand-activated transcription factors that are expressed in both vascular endothelial and smooth muscle cells. We recently demonstrated that long-term (8 d) estrogen treatment in vivo in mice recruits distinct vascular gene sets mediated by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
23
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 57 publications
3
23
0
Order By: Relevance
“…9, 16, 17 However, we recently demonstrated that many ER-regulated genes in the mouse aorta are down-regulated rather than up-regulated. 18, 19 Similar findings have been demonstrated in other, non-vascular cells as well. 20 The molecular mechanisms by which ERs repress gene expression are currently unknown.…”
supporting
confidence: 77%
See 1 more Smart Citation
“…9, 16, 17 However, we recently demonstrated that many ER-regulated genes in the mouse aorta are down-regulated rather than up-regulated. 18, 19 Similar findings have been demonstrated in other, non-vascular cells as well. 20 The molecular mechanisms by which ERs repress gene expression are currently unknown.…”
supporting
confidence: 77%
“…19 3 aortas were pooled for each assay. For each treatment group, miR arrays and real-time PCR were performed in duplicate and quadruplicate, respectively, as described below.…”
Section: Methodsmentioning
confidence: 99%
“…Total vessel RNA was isolated and reverse transcribed, and QRT-PCR was carried out as previously described (56) with primers specific for PGF, Flt1, or Flk1 (see Supplemental Table 2 for primer sequences). The CT value for each gene was normalized to that of β2-microglobulin (for mouse tissues) or GAPDH (for human tissues) and expressed as fold change in treated samples compared with normal or vehicle-treated samples as previously described (56). Between 3 and 6 mouse or human vessels were used for each condition.…”
Section: Methodsmentioning
confidence: 99%
“…qPCR was performed using SYBR Green Master Mix (QIAGEN), with each PCR performed in triplicate. Gene expression levels were normalized to ␤ 2 -microglobulin (a well-established normalization control for E 2 -regulated gene expression in mouse tissues) (30,31) and ER␣ binding was normalized to an intergenic region with no detectable ER␣ binding in mouse tissues (Brown, M., and J. Cook, personal communication). We tested 11 genes that were called by RNA-Seq as at least 1.35-fold differentially regulated by E 2 between tissues ([AoE Ϫ AoV] Ϫ [LiE Ϫ LiV]) by qRT-PCR (not all of which also met the P Ͻ .05 and fold change Ͼ1.5 cutoffs for inclusion in the lists of regulated genes by RNA-Seq).…”
Section: Qpcrmentioning
confidence: 99%
“…We examined gene regulation by estrogen in mouse aorta and liver using an established ex vivo treatment model (30). Female C57/BL6 mice, aged 6 to 7 weeks, were ovariectomized to remove the principal source of endogenous circulating estrogen (9).…”
Section: Estrogen Induces Tissue-specific Patterns Of Gene Expressionmentioning
confidence: 99%